The Impacts of Active Consumers’ Engagement with Social Media Brand-related Content (CESBC) on Instagram in Luxury Jewellery Market - Wu, Lingyi (2019)
Recently, electronic word-of-mouth (eWOM) has been found to have a significant impact on consumers' purchase decisions. Considering that people spend more and more time on social platforms, eWOM on social platforms could influence consumers strongly. At the same time, consumers' engagement with a brand can also enhance the understanding and attitude toward the brand. It is hard for brands to control eWOM on social media directly. In order to guide consumers to contribute to eWOM on social platforms, brands need to know how could the consumer engagement on social platforms affects consumers’ purchase intention. This study focuses on active consumers’ engagement with brand-related content (CESBC), which is considered to belong to both consumer engagement and eWOM. These active CESBC behaviours can affect other consumers and can also change consumers’ perception of engaged brands. This paper investigates the impact of active CESBC in the luxury jewellery market on Instagram on self-brand connection and brand attitude. Also, this paper investigates the relationship between self-brand connection and brand attitude, brand attitude and purchase intention, self-brand connection and purchase intention in the same context. Quantitative research is used in this study by publishing online surveys. The results show that contribution and creation have a positive impact on brand attitude and self-brand connection in the luxury jewellery market on Instagram. Besides, the positive relationships between self-brand connection and brand attitude, brand attitude and purchase intention, self-brand connection and purchase intention are be verified.